2006
DOI: 10.1007/s11103-006-9033-y
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose deficiency delays lycopene accumulation in tomato fruit pericarp discs

Abstract: Tomato (Solanum lycopersicum) fruit ripening is characterized by a massive accumulation of carotenoids (mainly lycopene) as chloroplasts change to chromoplasts. To address the question of the role of sugars in controlling carotenoid accumulation, fruit pericarp discs (mature green fruits) were cultured in vitro in the presence of various sucrose concentrations. A significant difference in soluble sugar content was achieved depending on external sucrose availability. Sucrose limitation delayed and reduced lycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 63 publications
2
72
1
Order By: Relevance
“…Sucrose was previously shown to promote a color break of citrus fruit epicarp (Iglesias et al 2001). Telef et al (2006) showed that sucrose availability favored lycopene biosynthesis in tomato fruit pericarp disks, and its effect on carotenoid accumulation was stronger than that of hexoses (glucose and fructose).…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose was previously shown to promote a color break of citrus fruit epicarp (Iglesias et al 2001). Telef et al (2006) showed that sucrose availability favored lycopene biosynthesis in tomato fruit pericarp disks, and its effect on carotenoid accumulation was stronger than that of hexoses (glucose and fructose).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, considerable changes in the metabolite composition have been observed that reside from perturbed carotenoid formation. Other studies have also reported in situ manipulation of sucrose levels altering carotenoid formation (Té lef et al, 2006). Presumably this illustrates the difference between systems that have been intentionally perturbed and unmodified physiological conditions.…”
Section: Online)mentioning
confidence: 97%
“…Isoprenoids were extracted and analyzed as described (Fraser et al, 2000) with slight modification (Te´lef et al, 2006). Briefly, 10 mg of lyophilized sample were mixed using a hand-held homogenizer with 1 mL of methanol and then 1 mL of Tris-HCl buffer (0.05 M, pH 7.5).…”
Section: Extraction and Lc Analysis Of Isoprenoidsmentioning
confidence: 99%
“…The pooled chloroform extracts were dried under a stream of nitrogen, immediately resuspended in 200 lL of ethyl acetate and injected into the HPLC system. Isoprenoid separation, identification and quantification were as described in Te´lef et al (2006).…”
Section: Extraction and Lc Analysis Of Isoprenoidsmentioning
confidence: 99%